Τα ευγενή μέταλλα : στοιχεία βιογραφίας : πεζά κείμενα - Κοντός, Γιάννης, 1943-2015 (Κέδρος, 1994)
Μέλπω Αξιώτη, Γιώργος Ιωάννου, Νικόλαος Κάλας, Ανδρέας, Κάλβος, Νανά Καλλιανέση, Τζένη Καρέζη, Μανόλης Αναγνωστάκης, Βασίλης Βασιλικός, Νέλλα Γκόλαντα, Παναγιώτης Γράββαλος, Νίκη Καραγάτση κ.α.